An investigation into genetic improvement in reproductive efficiency in beef cattle through the unravelling of composite reproductive traits - Rust, Tina (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD(Agric))--University of Stellenbosch, 2007.